2000
DOI: 10.1177/0093854800027003003
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi-Experimental Evaluation of an Intensive Rehabilitation Supervision Program

Abstract: Over the past 20 years, an increased understanding has been developed of what interventions do and do not work with offenders. Treatment programs that attend to offender risk, needs, and responsivity factors have been associated with reduced recidivism. There is also a recognition that sanctions without a rehabilitative component are ineffective in reducing offender recidivism. This study evaluates a cognitive-behavioral treatment program delivered within the context of intensive community supervision via elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(114 citation statements)
references
References 19 publications
6
103
0
5
Order By: Relevance
“…Results that contradict with each other may have been the result in the varying definitions of recidivism [14,15]. Unfortunately, early evaluations methodological problems also characterize outcome studies nearly 20 years after the implementation of EM programs (Bonta et al [16]), findings from researches that sought to address these problems are discouraging. In the widely cited Canadian study by Bonta et al [17], for example, the authors found that once risk level was taken into consideration, EM offenders no longer showed significant difference in recidivism rates compared to groups of offenders who were on probation EM and those released directly into the community with no such conditions imposed.…”
Section: Potential Problems/biasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results that contradict with each other may have been the result in the varying definitions of recidivism [14,15]. Unfortunately, early evaluations methodological problems also characterize outcome studies nearly 20 years after the implementation of EM programs (Bonta et al [16]), findings from researches that sought to address these problems are discouraging. In the widely cited Canadian study by Bonta et al [17], for example, the authors found that once risk level was taken into consideration, EM offenders no longer showed significant difference in recidivism rates compared to groups of offenders who were on probation EM and those released directly into the community with no such conditions imposed.…”
Section: Potential Problems/biasesmentioning
confidence: 99%
“…Recent studies on the probability to re-offend on low-risk offenders have been made whether they are under the EM programs or not. Moreover, most studies conclude that it is not the EM programs that have brought positive effects but on the risk level of offenders [16].…”
Section: Potential Problems/biasesmentioning
confidence: 99%
“…Rather, a significant body of research indicates that imprisonment might have a criminogenic effect [68,129]. 27 While the empirical evidence to support EM as a long-term rehabilitative tool is lacking, EM shows potential. If programs are designed with therapeutic considerations in mind [154], the indications are that EM offers significant advantages over prison in this regard.…”
Section: (A) Incapacitationmentioning
confidence: 99%
“…For example, the threat of relatively short, but certain, periods of imprisonment has proven to be an effective deterrent [91,211]. The large qualitative difference 27 Reasons for prison's poor rehabilitative record include in-prison rehabilitation programs typically not according with established principles of effective treatment, factors associated with reduced recidivism not being able to be optimally addressed in prison, and inmate exposure to criminogenic factors in the prison environment (such as prison being a criminal learning environment, strengthening antisocial bonds and weakening prosocial bonds, stigmatizing offenders, and exacerbating other identified correlates of criminal activity, such as unstable employment or housing) ( [129], pp.126-128; [3,119]). between prison and EM may limit EM's ability to deter crime, if it is not seen as sufficiently "distasteful" ( [68], p. 36).…”
Section: (C) Deterrencementioning
confidence: 99%
See 1 more Smart Citation